Opportunities and Challenges for Gut Microbiota in Acute Leukemia - Ma, Tao; Chen, Yan; Li, Li-Juan; Zhang, Lian-Sheng (Frontiers in Oncology, 2021)
Acute leukemia (AL) is a highly heterogeneous hematologic malignancy, and although great progress has been made in the treatment of AL with allogeneic hematopoietic stem cell transplantation (Allo-HSCT) and new targeted drugs, problems such as infection and GVHD in AL treatment are still serious. How to reduce the incidence of AL, improve its prognosis and reduce the side effects of treatment is a crucial issue. The gut microbiota plays an important role in regulating disease progression, pathogen colonization, and immune responses. This article reviews recent advances in the gut microbiota and AL pathogenesis, infection, treatment and its role in allo-HSCT.